Qualität der Chirurgie als Prognosefaktor beim Rektumkarzinom nach neoadjuvanter Radiochemotherapie - Brunner, M.; Perrakis, Aristotelis; Merkel, Susanne; Weber, K.; Grützmann, Robert (Chirurgische Praxis, 2019)
The prognosis of patients with rectal carcinoma has improved significantly in recent years, in particular through the introduction of TME (total mesorectal excision) surgery and neoadjuvant therapy with radiation or chemoradiotherapy in locally advanced carcinomas. Even in the era of TME surgery and neoadjuvant chemoradiation high-quality surgical therapy plays an important role for the prognosis of patients with rectal cancer, especially for local tumor control. Prognostically relevant surgical quality indicators represent the quality of TME, the R0 resection, the negative circumferential resection margin (CRM) and the avoidance of intraoperative local tumor cell dissemination. These four factors mainly affect the local recurrence rate, but are also significant in terms of overall survival.
CRIS-Team Scopus Importer:2021-04-20
Keywords: Neoadjuvant therapy; Preoperative chemoradiation; Prognostic factors; Quality of surgery; Rectal carcinoma; TME